2016
DOI: 10.3390/ma9050381
|View full text |Cite
|
Sign up to set email alerts
|

Higher Ratios of Hyaluronic Acid Enhance Chondrogenic Differentiation of Human MSCs in a Hyaluronic Acid–Gelatin Composite Scaffold

Abstract: Mesenchymal stem cells (MSCs) seeded on specific carrier materials are a promising source for the repair of traumatic cartilage injuries. The best supportive carrier material has not yet been determined. As natural components of cartilage’s extracellular matrix, hyaluronic acid and collagen are the focus of biomaterial research. In order to optimize chondrogenic support, we investigated three different scaffold compositions of a hyaluronic acid (HA)-gelatin based biomaterial. Methods: Human MSCs (hMSCs) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
0
29
1
Order By: Relevance
“…In fact, a recent study also showed that supplementation with HA leads to a lower expression of collagen type II (Amann, Wolff, Breel, van Griensven, & Balmayor, ). These results disagreed with another recent study, which indicated that higher HA resulted in a higher expression of chondrogenic gene marker genes at Days 1, 4, and 7 (Pfeifer et al, ). However, it should be noted that such an enhancement was not observed after a longer culture (21 days).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent study also showed that supplementation with HA leads to a lower expression of collagen type II (Amann, Wolff, Breel, van Griensven, & Balmayor, ). These results disagreed with another recent study, which indicated that higher HA resulted in a higher expression of chondrogenic gene marker genes at Days 1, 4, and 7 (Pfeifer et al, ). However, it should be noted that such an enhancement was not observed after a longer culture (21 days).…”
Section: Resultscontrasting
confidence: 99%
“…In (b), no statistical difference was found (n = 4) [Colour figure can be viewed at wileyonlinelibrary.com] FIGURE 3 Expression of chondrogenic (SOX 9, AGG, and COL2) and hypertrophic (COL10) marker genes in cells within different constructs was examined after 8 weeks (n = 4) with HA leads to a lower expression of collagen type II (Amann, Wolff, Breel, van Griensven, & Balmayor, 2017). These results disagreed with another recent study, which indicated that higher HA resulted in a higher expression of chondrogenic gene marker genes at Days 1, 4, and 7 (Pfeifer et al, 2016). However, it should be noted that such an enhancement was not observed after a longer culture (21 days).…”
Section: Figurementioning
confidence: 79%
“…Combining the advantages offered by gelatin and HA towards chondrocytes, gelatin/HA scaffolds (including cryogel scaffolds) have been shown to be suitable for applications in cartilage tissue engineering [16,17,18,19]. Nonetheless, from a tissue engineering point of view, the incorporation of a bioactive signal molecule into gelatin/HA scaffolds to promote chondrogenesis seems to be a rational approach to further enhance their functions.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al demonstrated superior chondrogenic differentiation of MSC embedded in Col compared to MSC only in a rat model [50]. On the other hand, HA has been combined with Col 1 or gelatin before with similar outcomes that chondrogenic differentiation is promoted in the composite compared to HA or Col only [51][52][53]. One limitation of the present technique is the shear-induce alignment, limiting the degrees of spatial freedom in fibril arrangement.…”
Section: Discussionmentioning
confidence: 92%